2005
DOI: 10.1159/000088099
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Atherogenic Effect of Insulin in vivo

Abstract: Metabolic syndrome is a risk factor for atherosclerosis and restenosis. In metabolic syndrome, insulin resistance coexists with hyperinsulinemia and hyperlipidemia. Hyperlipidemia has growth-promoting effects, whereas insulin has both growth-promoting and growth-inhibitory effects on vascular smooth muscle cells in vitro. The objective of this study was to investigate the effects of hyperlipidemia and hyperinsulinemia on vascular cell growth in vivo after arterial injury. Rats fed a low-fat diet were treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 58 publications
3
27
2
Order By: Relevance
“…6,7 At higher plasma concentrations (Ϸ2000 pmol/L) we previously found that insulin does increase intimal cell proliferation despite decreasing neointimal growth. 36 Taken together, these data suggest that the effect of insulin is dose-, time-, and cell-type dependent. IGF-1, which shares similar signaling with that of insulin but preferentially stimulates MAPK versus PI3K, increased intimal thickness.…”
Section: Discussionmentioning
confidence: 83%
“…6,7 At higher plasma concentrations (Ϸ2000 pmol/L) we previously found that insulin does increase intimal cell proliferation despite decreasing neointimal growth. 36 Taken together, these data suggest that the effect of insulin is dose-, time-, and cell-type dependent. IGF-1, which shares similar signaling with that of insulin but preferentially stimulates MAPK versus PI3K, increased intimal thickness.…”
Section: Discussionmentioning
confidence: 83%
“…The rats were divided into 6 groups: (1) rats with blank implants and access to tap water (control = C); (2) rats with insulin implant (5 U/day) and access to glucose in their drinking water as a 40% (w/v) solution [insulin (5 U/day) + 40% oral glucose = I5G] as in Kim et al [9] but with i.p. glucose infusion (25%) to avoid any glucose lowering; (3) rats with insulin implant (4 U/day, which is similar to ∼3.9 U/day used in Foster et al [16]) and access to glucose in their drinking water as a 40% (w/v) solution [insulin (4 U/day) + 40% oral glucose = I4G]; (4) rats with insulin implant (4 U/day) and access to sucrose in their drinking water as a 10% (w/v) solution as in Foster et al [16] [insulin (4 U/day) + 10% oral sucrose = I4S]; (5) rats with blank implants and access to glucose in their drinking water as a 40% (w/v) solution (control glucose = CG), and (6) rats with blank implants and access to sucrose in their drinking water as 10% (w/v) solution (control sucrose = CS).…”
Section: Methodsmentioning
confidence: 99%
“…glucose infusion (25%) to avoid any glucose lowering; (3) rats with insulin implant (4 U/day, which is similar to ∼3.9 U/day used in Foster et al [16]) and access to glucose in their drinking water as a 40% (w/v) solution [insulin (4 U/day) + 40% oral glucose = I4G]; (4) rats with insulin implant (4 U/day) and access to sucrose in their drinking water as a 10% (w/v) solution as in Foster et al [16] [insulin (4 U/day) + 10% oral sucrose = I4S]; (5) rats with blank implants and access to glucose in their drinking water as a 40% (w/v) solution (control glucose = CG), and (6) rats with blank implants and access to sucrose in their drinking water as 10% (w/v) solution (control sucrose = CS). The rats were fed a normal-fat diet, consisting of 12% fat in calories as used in Kim et al [9]. This diet, despite having the same fat content of the standard chow used in another study where we found insulin to decrease neointimal growth [11], was defined as low-fat in Kim et al [9] to contrast it to the high-fat diet also used in that paper.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations